Design of Library Information Systems for Collections Procurement at Hayam Wuruk Perbanas Library - Aditya Ramadhani; Dio Eka Prayitno (Universitas Airlangga, 2022)
Information disclosure is an opportunity and a challenge for libraries in managing information. Management of this information must be done quickly and precisely so that people can consume information according to their needs. Libraries take an important role in such conditions because the library as an information management organization has a strategic role so that the information circulating can be in accordance with the needs of the community. Up-to-date information is one way for the public to get appropriate information and this must be done by the library so that the existence and value of its benefits can be felt by the community. The community can take a role in supporting the updating of the information. One way to keep the information up to date is to adjust the collection of library materials by conducting it. The approach that is owned by the library is to monitor the process of procuring a collection of library materials carried out by the library. Librarians can build an information system design that can accommodate these activities. The research method used in this article is a research with a qualitative descriptive approach in the form of a case study. This article aims to offer an information system for the procurement of library material collections carried out by the Hayam Wuruk Perbanas University Surabaya Library. The result is a proposed information system for the procurement of a new collection of library materials with an open nature so that all stages or the process of procuring a collection of library materials can be monitored together and users can find out the up-to-date collection of library materials owned by the library.